2007
DOI: 10.1097/qai.0b013e3180f616db
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Changes in Sexual Behavior by Female Sex Workers After Completion of a Randomized HIV Prevention Trial

Abstract: Less intensive community-based risk reduction services after clinical trial termination may support ongoing reductions in STIs and HIV among high-risk FSWs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…However, reported condom use was significantly lower with primary partners even though women were unlikely to know any partners' HIV status, suggesting that FSW were still unable to negotiate condom use with long-term partners or did not want to use condoms perhaps because these partners are considered less risky. 17 Such partner-specific condom use has been seen in other FSW and female cohorts in a variety of settings [18][19][20] and supports the concept that HIV prevention methods that are controlled by or can be detected by male partners may not be feasible for women in primary partnerships. Completely discrete intravaginal products, oral preexposure prophylaxis, or vaccines may be the only types of methods that can overcome this barrier.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, reported condom use was significantly lower with primary partners even though women were unlikely to know any partners' HIV status, suggesting that FSW were still unable to negotiate condom use with long-term partners or did not want to use condoms perhaps because these partners are considered less risky. 17 Such partner-specific condom use has been seen in other FSW and female cohorts in a variety of settings [18][19][20] and supports the concept that HIV prevention methods that are controlled by or can be detected by male partners may not be feasible for women in primary partnerships. Completely discrete intravaginal products, oral preexposure prophylaxis, or vaccines may be the only types of methods that can overcome this barrier.…”
Section: Discussionmentioning
confidence: 85%
“…14,20,22,24 However, the cohort described here is particularly relevant for biomedical HIV prevention trials because of the high HIV incidence observed. Recent studies of HIV incidence in FSW cohorts in other areas of Nairobi have found lower incidence rates that would not support participation in efficacy trials.…”
Section: Discussionmentioning
confidence: 99%
“…G. Williams et al, 2003) in consistent condom use. Increase in condom use for different FSW partner types was measured in some studies and consistent condom use was less with intimate partners of FSWs (boyfriends and non-paying regular partners) than with paying clients (Feldblum et al, 2005;Nagot et al, 2005;Ngugi et al, 2007;Odek et al, 2009;Raul et al, 2002;Ray et al, 2001;Steen et al, 2000;Thomsen et al, 2006;Wechsberg et al, 2006). Considerable loss to follow-up was reported in some of the studies with a few showing high attrition rates of greater than 50% (Feldblum et al, 2005;Ngugi et al, 2007;Ray et al, 2001;Walden et al, 1999;B.…”
Section: Effectivenessmentioning
confidence: 99%
“…Twelve studies combined various methods for the delivery of condom use messages (Asamoah-Adu et al, 1994;Carney, Petal, Petersen, & Parry, 2016;Feldblum et al, 2005;Ghys et al, 2002;Lutchters et al, 2008;Nagot et al, 2005;Ngugi et al, 2007;Ngugi, Wilson, Sebstad, Plummer, & Moses, 1996;Odek et al, 2009;Parcesepea et al, 2016;Pickering, Quigley, Pépin, Todd, & Wilkins, 1993 ;B. G. Williams et al, 2003;E.…”
Section: Effectivenessmentioning
confidence: 99%
“…All studies report that sex workers who do use contraception resort most often to condoms yet the latter are not consistently used in all sex acts 3,[5][6][7][8][9] . FSWs may have difficulties in negotiating the consistent use of condoms with clients, and also may deliberately use condoms with some types of partners (such as casual clients) while deliberately not using condoms with other types of partners (such as emotional partners or regular clients) 10 . The consistency of condom use is a critical consideration when evaluating its role in reducing unmet need for contraception, not to mention HIV/ STI prevention.…”
Section: Introductionmentioning
confidence: 99%